2021
DOI: 10.3389/fmicb.2020.574053
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the GEMs: Genotype, Environment, and Microbiome Interactions Shaping Host Phenotypes

Abstract: One of the fundamental tenets of biology is that the phenotype of an organism (Y) is determined by its genotype (G), the environment (E), and their interaction (GE). Quantitative phenotypes can then be modeled as Y = G + E + GE + e, where e is the biological variance. This simple and tractable model has long served as the basis for studies investigating the heritability of traits and decomposing the variability in fitness. The importance and contribution of microbe interactions to a given host phenotype is lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…In particular, the discontinuity of sweeps in microbiome QTL regions suggests that evolutionary pressure for recombination of key (microbiome associated) traits, such as iron homeostasis and water transport, may have acted against selective sweeps. The results obtained here provide the means to illuminate such complex eco-evolutionary questions, forming the basis of integrating the microbiome into the classic genotype by environment model of host phenotype 10 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the discontinuity of sweeps in microbiome QTL regions suggests that evolutionary pressure for recombination of key (microbiome associated) traits, such as iron homeostasis and water transport, may have acted against selective sweeps. The results obtained here provide the means to illuminate such complex eco-evolutionary questions, forming the basis of integrating the microbiome into the classic genotype by environment model of host phenotype 10 .…”
Section: Discussionmentioning
confidence: 94%
“…Developing a blueprint of the genetic architecture for this 'chemical dialogue' and how these interactions lead to specific MAPs is a one of the key focal points in current plant microbiome research. The promise is that these genomic and chemical blueprints can be integrated into microbiome breeding programs for a new generation of crops that can rely, in part, on specific members of the microbiome for stress protection, enhanced growth and higher yields 10 .…”
Section: Mainmentioning
confidence: 99%
“…There are limitations in the assumptions made by existing methodologies, such as GWAS, that directly attribute plant phenotypes to environmental variables. These methods do not explicitly incorporate biological and molecular interactions, such as post-translational modification of macromolecules [16], the importance of plant-microbe interactions [17], or endogenous siRNA [18]. However, a machine learning approach allows for these biological phenomena to be accounted for as latent variables while probing the interactions of genomes, environments, and phenotypes in a multidimensional manner.…”
Section: Challenges Of Dataset Interoperabilitymentioning
confidence: 99%
“…Starting from these evidences, many studies demonstrated that the host plays an active role in shaping its symbiont microbiota (Augustin et al, 2017; Franzenburg et al, 2012; Fraune & Bosch, 2007; Groussin et al, 2017; Lee et al, 2016). In addition to the effects of the host and the environment, the interaction between these two factors is also discussed as a potential factor influencing the plasticity of the microbiota (Oyserman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%